2010
DOI: 10.1016/j.neuroscience.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Tooth pulp inflammation increases brain-derived neurotrophic factor expression in rodent trigeminal ganglion neurons

Abstract: Nociceptive pathways with first-order neurons located in the trigeminal ganglion (TG) provide sensory innervation to the head, and are responsible for a number of common chronic pain conditions, including migraines, temporomandibular disorders and trigeminal neuralgias. Many of those conditions are associated with inflammation. Yet, the mechanisms of chronic inflammatory pain remain poorly understood. Our previous studies show that the neurotrophin brain-derived neurotrophic factor (BDNF) is expressed by adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
2
33
0
3
Order By: Relevance
“…IHC for BDNF on guinea pig trigeminal ganglion sections for the antibody positive control demonstrated that some neurons with small cell bodies were labeled strongly, consistent with reported results in the literature (Gunjigake et al 2006;Tarsa et al 2010) and indicating the efficacy of the antibody and IHC prototol used in our study (Fig. 5).…”
Section: Bdnf Expression In Human Cochleasupporting
confidence: 91%
See 1 more Smart Citation
“…IHC for BDNF on guinea pig trigeminal ganglion sections for the antibody positive control demonstrated that some neurons with small cell bodies were labeled strongly, consistent with reported results in the literature (Gunjigake et al 2006;Tarsa et al 2010) and indicating the efficacy of the antibody and IHC prototol used in our study (Fig. 5).…”
Section: Bdnf Expression In Human Cochleasupporting
confidence: 91%
“…For the positive control for the BDNF antibody, cryo-sections of guinea pig trigeminal ganglion fixed and sectioned by the same methods as those for human cochlea were subjected to IHC for BDNF. We used this tissue because, in rodent trigeminal ganglion, a substantial number of small BDNF-positive neurons have been constantly revealed (Gunjigake et al 2006;Tarsa et al 2010).…”
Section: Ihc and Immunocytochemistrymentioning
confidence: 99%
“…In addition, heat hyperalgesia in the whisker pad skin was depressed by daily application of neutralizing anti-NGF antibody to the inflamed lower lip or a nonspecific tyrosine kinase inhibitor K252a into TG ipsilateral to the inflamed lower lip. BDNF, which is TrkB ligand, is released from TG neurons by neuronal hyperexcitability (Buldyrev et al, 2006), and also tooth pulp inflammation significantly increased BDNF-and TRPV1-positive TG neurons (Tarsa et al, 2010). Because K252a inhibits tyrosine kinase, TrkB and TrkC inhibition by K252a may also be involved in depression of the heat hyperalgesia in whisker pad skin.…”
Section: Involvement Of Trpv1 In Heat Hyperalgesiamentioning
confidence: 99%
“…Previous studies by our group indicate that BDNF is a candidate mediator of plasticity at first-order synapses in trigeminal nociceptive pathways (Buldyrev et al, 2006), with implications for pathophysiology of migraine and other primary headaches (Latremoliere and Woolf, 2009). Our recent studies show that inflammation within peripheral endings of trigeminal nociceptors dramatically upregulates BDNF in trigeminal ganglion (TG) neurons in vivo (Tarsa et al, 2010). However, the cellular mechanisms underlying the inflammation-induced BDNF upregulation remain unknown.…”
mentioning
confidence: 99%